Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Pengelolaan Keuangan Mahasiswa Yang Bekerja (Studi Kasus Universitas Di Kota Palembang) - Pransiska, Reni; Indriani, Poppy (CV. ITTC INDONESIA, 2024)
This research aims to test the hypothesis of the influence of financial literacy and lifestyle on financial management. The population in this study were university students in the city of Palembang. This research data was obtained from the results of a questionnaire with the criteria of students studying while working for university students in the city of Palembang, the sample size was 100 students. The method in this research is quantitative associative (causal) with multiple linear regression analysis techniques. The results of the hypothesis test concluded that partially there is an influence between financial literacy on financial management, lifestyle does not have a significant influence on financial management and simultaneously there is an influence of financial literacy and lifestyle variables on financial management.